The Convergence of CAPTURED Fish and People: Examining the Symbiotic Nature of Labor Trafficking and Illegal, Unreported and Unregulated Fishing. Issue 6 (2nd June 2020) - Moreto, William D.; Charlton, Richard W.; DeWitt, Samuel E.; Burton, Christina M.
ABSTRACT: Environment crime has received considerable attention from criminologists in recent years. Not only have scholars examined the social, political, cultural, and situational factors that influence environment crime, but researchers have also explored the potential overlap of environment crime with other criminal activities, including transnational organized crime and corruption. One line of inquiry, however, that has received little attention is the intersection between environment crime and labor trafficking. The present study assesses the convergence of labor trafficking and the illegal fishing industry through the theoretical lens of crime symbiosis and the CAPTURED framework. Implications for theory and policy are also outlined.